2010
DOI: 10.1902/jop.2010.090621
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ultrasonic Device to Measure the Distance From the Bottom of the Osteotome to Various Anatomic Landmarks

Abstract: The results of this in vivo study support the value of this ultrasonic system in measuring the residual osseous depth from the bottom of the osteotome to the roof of the IAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…These factors may be responsible for the fact that the device has not become part of the standard armamentarium of the clinician. Nevertheless, the ultrasound has a broad application in various dental fields: to measure blood supply to alveolar bone, to evaluate bone quantity and quality before implantation, to try to improve hard and soft tissue healing and accelerate osseointegration of dental implants, to locate submerged implants installed in a two‐stage protocol, and even to measure the residual osseous depth from the bottom of the osteotome to various anatomic landmarks …”
Section: Discussionmentioning
confidence: 99%
“…These factors may be responsible for the fact that the device has not become part of the standard armamentarium of the clinician. Nevertheless, the ultrasound has a broad application in various dental fields: to measure blood supply to alveolar bone, to evaluate bone quantity and quality before implantation, to try to improve hard and soft tissue healing and accelerate osseointegration of dental implants, to locate submerged implants installed in a two‐stage protocol, and even to measure the residual osseous depth from the bottom of the osteotome to various anatomic landmarks …”
Section: Discussionmentioning
confidence: 99%
“…34 Accurate bone height evaluation above the mandibular canal is essential when planning a posterior implant as insertion of an inadequately long implant can injure the inferior alveolar nerve resulting in permanent hypoesthesia of the lower lip. Machtei et al 35 measured the distance from the apex of a pilot drill to the roof of the inferior alveolar canal on a digital panoramic radiograph (Planmeca Proline XC; Planmeca, Helsinki, Finland; mean 5.18 ± 0.61 mm) and compared it with the readings of an ultrasonic device used to measure the distance from the bottom of the osteotome preparation to the canal (mean 5.26 ± 0.61). They found a strong and highly significant correlation between the two measurement methods, indicating that digital panoramic radiographs have the measurement precision and accuracy required to determine pre-operative implant length for use in the posterior mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated a strong positive correlation between US and radiographic measurements in the mandible; nevertheless, a nonsignificant and weak correlation was found in the maxilla. Based on these results, we have concluded that the tested US device may serve as a useful intraoperative tool to measure the distance from osteotomy to the mandibular canal . Therefore, the aim of the current, prospective clinical trial was to validate our previous results in a larger group of osteotomies in the posterior mandible.…”
Section: Introductionmentioning
confidence: 81%
“…However, when we dichotomized the results into maxilla and mandible, we found a strong positive correlation between radiographic and US measurements in the mandible, but a weak and nonsignificant correlation in the maxilla. We assumed that these results could be related to difficulties in identifying the floor of the maxillary sinus on panoramic views . Therefore, in the present study we measured only mandibular osteotomies.…”
Section: Discussionmentioning
confidence: 99%